Subtract (3.4+−25−−−−√)−(−9−−9−−−√)%0D%0A(%0D%0A3.4%0D%0A+%0D%0A−%0D%0A25%0D%0A)%0D%0A−%0D%0A(%0D%0A−%0D%0A9%0D%0A−%0D%0A−%0D%0A9%0D%0A)%0D%0A. Provide your answer in the form of a+bi%0D%0A𝑎%0D%0A+%0D%0A𝑏%0D%0A𝑖%0D%0A.(

1 answer

To solve the expression \((3.4 + \sqrt{-25}) - (\sqrt{-9})\), we first need to identify the square roots of the negative numbers involved.

  1. Calculate the square roots:

    • \(\sqrt{-25} = \sqrt{25} \cdot \sqrt{-1} = 5i\)
    • \(\sqrt{-9} = \sqrt{9} \cdot \sqrt{-1} = 3i\)
  2. Substitute the square roots back into the expression: \[ (3.4 + 5i) - (3i) \]

  3. Simplify: \[ 3.4 + 5i - 3i = 3.4 + (5i - 3i) = 3.4 + 2i \]

Thus, the result in the form \(a + bi\) is: \[ \boxed{3.4 + 2i} \]